ANALISA LIKUIDITAS PADA KOPERASI UNIT DESA USPEK DI DESA URAUR - DANIEL Y. TITAPASANEA (P3M Politeknik Negeri Ambon, 2022)
KUD USPEK manages its capital for the continuity of its business by using all of its own resources, but it is also possible to use a policy to use capital that comes from outside KUD in the form of obligations to other parties. To carry out its daily activities in providing services to consumers, the USPEK KUD also needs to assess the short-term financial position so that the KUD management can find out how much ability the USPEK KUD has in completing short-term obligations.By using a liquidity ratio analysis that includes the Current Ratio, Acid Test Ratio and Cash Ratio to determine the ability of the USPEK KUD to pay all of its short term obligations.From the results of the discussion it can be concluded that in general it can be said that the USPEK KUD is said to be liquid except for its cash ratio. Based on the results of the Current Ratio and Acid Test Ratio analysis, it can be said that the USPEK KUD in 2017 has not been able to pay off its short-term debt using current assets, while the cash ratio for 202017 and 2018 is said to be inliquid but in the following years it is able to pay all liabilities short term (liquid) and tends to increase every year. Keywords: Liquidity Ratio